Pollution characteristics and human health risks of potentially (eco)toxic elements (PTEs) in road dust from metropolitan area of Hefei, China. (August 2017) - Ali, Muhammad Ubaid; Liu, Guijian; Yousaf, Balal; Abbas, Qumber; Ullah, Habib; Munir, Mehr Ahmed Mujtaba; Fu, Biao
Abstract: This study aims to investigate the pollution characteristics of road dust and their associated health risks of potentially toxic elements (PTEs) to humans using array-based risk assessment models described by United States Environmental Protection Agency (USEPA) in a metropolitan area of Hefei, China. Geoaccumulation index (Igeo ) was used to describe pollution characteristics of roadside dust in urban, periurban and industrial areas. Results indicate that industrial roadside dust was contaminated with Fe, Ni, Cu, Ti, V, Pb, Ba, Sb, Cr, Sn, Pb, As and Ga showing I geo value ( log 2 ( x )) between Igeo class 3 to 4. In other hand, urban roadside dust contamination with Cu, Zn, Sb and Ga ranged between Igeo classes 2 to 3 and with As and Pb ranged between Igeo classes 4 to 5. Furthermore, health risk assessment revealed negligible non-cancerous health hazard in all sites including urban, periurban and industrial areas. The hazard quotient (HQ) and hazard Index (HI) values for all exposure routes (ingestion, inhalation, and dermal contact) were <1 except for chromium with HI value of 1.06E+00 in industrial areas. Moreover, the most prominent exposure route was ingestion (HQing ) and the non-carcinogenic health risks were found to be high in case of children compared to the adults. The cancer risk from As, Co, Cr, Ni, and Pb was found to be in safe levels as the RI (carcinogenic risks) values were below the limits for carcinogens (1.00E-6 to 1.00E-4). Graphical abstract: Highlights: Pollution characteristics of PTEs in roadside dust were assessed. Exposures to PTEs in road dust and their potential health risks were estimated. Distribution of most PTEs was affected by the industrial activities. As, Cu, Pb, Sn and Zn concentrations in urban areas were found to be higher than industrial areas. Potential health risks of PTEs were lower than regulatory guideline levels.